2022
DOI: 10.1101/2022.07.13.22277479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms linking physical activity with psychiatric symptoms across lifespan: A systematic review

Abstract: Background: Physical activity has been suggested as a protective factor against psychiatric symptoms. While numerous studies have focused on the magnitude of the effect of physical activity on psychiatric symptoms, few have examined the potential mechanisms. Objective: The current review aimed to synthesize scientific evidence of the mechanisms through which physical activity might reduce psychiatric symptoms across the lifespan. Methods: We included articles that were published before March 2022 from five e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
(219 reference statements)
1
2
0
Order By: Relevance
“…with greater maturity during adolescence, which might help them deal with new life circumstances (eg, academic pressure and the influence of peers) and protect their mental health. This finding is consistent with a recent systematic review 41 wherein self-dimensions were the only consistent paths observed through which physical activity was associated with improvement in psychiatric symptoms in youth.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…with greater maturity during adolescence, which might help them deal with new life circumstances (eg, academic pressure and the influence of peers) and protect their mental health. This finding is consistent with a recent systematic review 41 wherein self-dimensions were the only consistent paths observed through which physical activity was associated with improvement in psychiatric symptoms in youth.…”
Section: Discussionsupporting
confidence: 92%
“…We did not observe any other mechanisms underlying the association of sports participation with internalizing symptoms. Accordingly, the aforementioned systematic review 41 showed the role of the neurobiological mechanisms in the association between physical activity and psychiatric symptoms is unclear, probably because of the inconsistencies and heterogeneity observed among included studies. For instance, previous studies have used MRI data as indicators of the neurobiological mechanisms while others have examined the role of blood circulating biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation